1999
DOI: 10.1002/(sici)1521-3935(19990201)200:2<405::aid-macp405>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

New aspects of thermal treatment effects on gelatin films studied by microhardness

Abstract: SUMMARY: Microhardness measurements were carried out using various treatment cycles, including heating and cooling during different treatment times at high temperatures. Two possible processes to explain the observed increase in the microhardness are proposed, namely crystallisation and crosslinking. In order to distinguish between these two alternatives, differential scanning calorimetry (DSC), wide-angle X-ray scattering (WAXS), and swelling kinetics measurements were performed. The observed decrease of crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The higher the bloom number, the more rigid a gelatin gel. 15 When gelatin is applied as a coating its mechanical properties depend on factors like temperature and thermal history, 16,17 water content, 18 source of gelatin 12 and bloom number. 19 Albeit this multitude of factors influences the properties of gelatin coatings, little systematic work has been published regarding the influence of different conditions during the coating process on the properties of the gelatin coated ceramics.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…The higher the bloom number, the more rigid a gelatin gel. 15 When gelatin is applied as a coating its mechanical properties depend on factors like temperature and thermal history, 16,17 water content, 18 source of gelatin 12 and bloom number. 19 Albeit this multitude of factors influences the properties of gelatin coatings, little systematic work has been published regarding the influence of different conditions during the coating process on the properties of the gelatin coated ceramics.…”
Section: Introductionsupporting
confidence: 92%
“…The weight loss of gelatin coating fragments measured with thermal gravimetry ranges at 14 wt% (80 and 250 gbloom, preparation temperature 50 • C, dried at room temperature before thermal analysis). This value for water content is in line with values reported in, 17 and is of similar value as that one (12 wt%) reported by Yakimets et al 18 below which no further increase in tensile strength can be expected. Hence, a further reduction in water content due to drying for 3 days at elevated temperatures did not result in an increase in compressive strength.…”
Section: Influence Of Gelatin Sol Temperature Bloom Number and Dryinmentioning
confidence: 99%
“…3) are very scattered, the only exception being the glutaric aldehyde crosslinked sample (2) where the microhardness increases linearly by a factor of 1.3 and this can be connected with the process of getting crystallites more perfect with the increase of the t a . This is con®rmed by the data for sample 2 in Table III.…”
Section: Mechanical Properties Of Gelatinmentioning
confidence: 99%
“…In our previous studies [1,2] it was found that the microhardness of native gelatin being relatively high as compared to other polymeric materials, dramatically increases with temperature and duration of thermal treatment of the samples. As native gelatin we consider chemically uncrosslinked gelatin ®lms obtained by casting of water solution at room temperature.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation